2019
DOI: 10.1007/978-3-030-27397-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Digitalizing Crisis Management Training

Abstract: The ongoing digital transformation in government has enabled innovative changes in operational processes and service. However, while e-services and social media are widely adopted, earlier studies indicate that this transformation is still being awaited in other areas, such as crisis or disaster preparedness. Recent events such as the 2018 wildfires in several parts of Europe, as well as empirical research, highlight the need for more (systematic) training of local governments' crisis management teams. Convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…The literature emphasises, that such strategic leadership is crucial for navigating organisational crises. For example, Magnusson et al (2019) identified a connection between the strategic plan and organisational outcomes. They suggest that a strategic management team that focuses on preventing crises when possible, and plans strategies for mitigating the effects of potential crises, when prevention is not possible, will help provide a template for crisis management policy decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The literature emphasises, that such strategic leadership is crucial for navigating organisational crises. For example, Magnusson et al (2019) identified a connection between the strategic plan and organisational outcomes. They suggest that a strategic management team that focuses on preventing crises when possible, and plans strategies for mitigating the effects of potential crises, when prevention is not possible, will help provide a template for crisis management policy decisions.…”
Section: Introductionmentioning
confidence: 99%